The Effect of Competition and Interest Rates on Sales Volume Through Service Quality - Mohammad Rahmat N; Andi Mappatompo; Buyung Romadhoni (Journal La Bisecoman, 2022)
PT Adira Finance is one of the companies engaged in services, the increasing number of Finance that has sprung up is one of the challenges of PT Adira Finance in maintaining and attracting new customers. The purpose of this study is to analyse the effect of competition, interest rates and sales volume through service quality. According to the results of SEM analysis based on data from questionnaires distributed to 185 respondents, it is known that competition has a significant effect on service quality, interest rates have a significant effect on service quality, sales volume has a significant effect on service quality, competition has a significant effect on sales volume through service quality with a coefficient value of 0.000, while interest rates do not have a significant effect on sales volume through service quality with a coefficient value of 0.055.